Clinical outcome of a highly flexible duodenal stent for gastric outlet obstruction: A multicenter prospective study. Issue 4 (17th March 2020) - Miwa, Haruo; Sugimori, Kazuya; Kaneko, Takashi; Ishii, Tomohiro; Iwase, Shigeru; Irie, Kuniyasu; Sanga, Katsuyuki; Tozuka, Yuichiro; Hirotani, Akane; Komiyama, Satoshi; Sato, Takeshi; Tezuka, Shun; et al.
Abstract: Background and Aim: Endoscopic duodenal stenting for patients with malignant gastric outlet obstruction (GOO) has been widespread; however, clinical trials evaluating the structures of duodenal stents are lacking. Thus, we aimed to investigate the clinical outcomes of a highly flexible duodenal stent for GOO patients. Methods: A prospective study of duodenal stenting for GOO patients from five hospitals between August 2017 and August 2018 was performed. WallFlex Duodenal Soft were used in all procedures. The primary endpoint was clinical success, defined as an improvement in the GOO scoring system. Results: The study enrolled 31 patients (12 women, 19 men) with GOO, with a median age of 70 (range 52–90) years. Primary diseases were pancreatic cancer, gastric cancer, biliary tract cancer, and others in 14, 10, 3, and 4 patients, respectively. The technical success rate was 97%, and the clinical success rate was 87%. Simultaneous biliary drainage was performed in 19% of patients. Adverse events occurred in three patients. Chemotherapy was given in 41% of clinically successful cases, and the median overall survival time after stent placement was 82 days (range, 30–341 days), and. Stent dysfunction occurred in 30% of clinically successful cases (stent ingrowth in seven and stent overgrowth in one patient). The median time to stent dysfunction was 157 days (range, 11–183 days). Six patients were treated with additional stent placement after dysfunction. Conclusion: Placement of a highly flexible duodenal stent is an effective and safe treatment for patients with GOO (UMIN‐CTR 000028783). Abstract : We evaluated the clinical outcome of a highly flexible duodenal stent for gastric outlet obstruction in this multicenter prospective study. Placement of WallFlex Duodenal Soft was an effective and safe procedure.